2001
DOI: 10.1111/j.1745-9125.2001.tb00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Policing Mentally Disordered Suspects: A Reexamination of the Criminalization Hypothesis*

Abstract: The criminalization hypothesis is based on the assumption that police inappropriately use arrest to resolve encounters with mentally disordered suspects. The current study uses data collected from two large-scale, multi-site field studies of police behavior-the Project on Policing Neighborhoods (POPN) conducted in 1996-1997 and the Police Services Study (PSS) conducted in 1977-to examine the relationship between suspect mental health and use of arrest by police.Multivariate results show that police are not mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
209
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(227 citation statements)
references
References 43 publications
13
209
2
2
Order By: Relevance
“…More recent research has also suggested that police officers are more likely to arrest individuals with a mental disorder (Teplin & Pruett, 1992), though the reverse has also been found (Engel & Silver, 2001;Watson, et al, 2004). This indicates that if MD suspects are viewed negatively, the way they are treated may be different due to the set of myths, stereotypes or beliefs that the MD label can evoke (Link et al, 1999;Scheff, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…More recent research has also suggested that police officers are more likely to arrest individuals with a mental disorder (Teplin & Pruett, 1992), though the reverse has also been found (Engel & Silver, 2001;Watson, et al, 2004). This indicates that if MD suspects are viewed negatively, the way they are treated may be different due to the set of myths, stereotypes or beliefs that the MD label can evoke (Link et al, 1999;Scheff, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, incident-level factors-such as the severity of the offense, the role of substance abuse or community priorities, and resulting police agency policies-were absent from these original studies (2). Furthermore, this work did not adequately consider the police decision-making process or police behavior-crucial elements of police discretion (18).…”
Section: The Criminalization Hypothesismentioning
confidence: 99%
“…In another test of the criminalization hypothesis, Engel and Silver (18) found that when the analyses controlled for other factors, police were less likely to arrest people with mental illness, compared with other suspects, and that mental illness can act in some models as a protective factor. These findings have been replicated in subsequent studies (19).…”
Section: The Criminalization Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of policing lend no support to the premise that officers systematically use arrest as a means of managing the behavior of persons with mental illness. For example, Engel and Silver (2001), analyzing data from two large-scale, multi-site studies of police behavior, found that police were in fact not more likely to arrest mentally disordered suspects. Another line of inquiry has examined the movement of persons with mental illness between settings operated by the mental health and criminal justice systems, one of the factors that led to Abramson's (1972) original raising of the criminalization issue.…”
Section: Testing the Criminalization Constructmentioning
confidence: 99%